Accountability and Transparency in Public Sector Accounting: A Systematic Review - Ratna Sari; Muslim Muslim (Amkop Management Accounting Review (AMAR), 2023)
This study aims to systematically review the mechanisms that promote accountability and transparency in public sector accounting, focusing on regulatory frameworks, auditing practices, digital transformation, stakeholder engagement, and ethical considerations. The study employs a systematic review design, following PRISMA guidelines to ensure a rigorous and transparent approach. The literature search spans from 2000 to 2023, including peer-reviewed journal articles, books, and official reports. Keywords such as "accountability in public sector accounting," "transparency in government financial reporting," and "public sector auditing" were used to identify relevant studies. Data was extracted and analyzed using qualitative synthesis and thematic analysis to identify patterns, themes, and gaps. The review highlights the significant role of IPSAS and GFS in enhancing financial transparency and accountability. Effective external and internal auditing practices are crucial for maintaining public trust. Digital technologies and e-government initiatives improve the accessibility and transparency of financial information, although challenges such as data security and digital literacy remain. Active stakeholder engagement and robust ethical frameworks are essential for fostering a culture of transparency and accountability. The findings underscore the need for a multifaceted approach to improving public sector financial management. Policymakers should prioritize adopting international standards, invest in digital infrastructure, and promote ethical behavior through continuous education. Future research should explore tailored support initiatives and the impact of emerging technologies on transparency and accountability.